What's New in Endocrinology: The Chromaffin Cell - Eiden, Lee E.; Jiang, Sunny Zhihong (Frontiers in Endocrinology, 2018)
Recent advances in understanding the intracellular and intercellular features of adrenal chromatin cells as stress transducers are reviewed here, along with their implications for endocrine function in other tissues and organs participating in endocrine regulation in the mammalian organism.